Waste valorization through additive manufacturing in an industrial symbiosis setting - Ferreira, Inês A. (2021)
Given the current environmental concerns related to manufacturing, the introduction to the industrial symbiosis concept brought purpose to waste, instead of disposing it in landfills or eliminating it through incineration. The waste generated by industrial processes, or end-of-life products, is redirected to be used as a “new” input in another process by one or more organizations, which is a mutual benefit or a “symbiosis”. Despite its relevancy, the industrial symbiosis concept is marginally explored in the context of additive manufacturing; this emerging technology has disruptive potential regarding the use of different materials as secondary raw materials. This paper presents a systematic literature review regarding industrial symbiosis and additive manufacturing. The main objective is to identify how wastes can be used as input materials to additive manufacturing processes and what exchanges of resources occur in an industrial symbiosis setting. A final sample of 32 documents was reached and analyzed. Five examples of using waste streams in additive manufacturing processes to produce goods were highlighted and explored.